The underpricing of initial public offerings in imperial Germany, 1870-1896 - Carsten Burhop (Max Planck Institute for Research on Collective Goods, 2008)
In this article, we evaluate underpricing of initial public offerings (IPOs) at the Berlin Stock Exchange between 1870 and 1896. In contrast to modern data, first day returns were extraordinary low and averaged less than five percent, even during the speculative period of the early 1870s. Moreover, standard underpricing theories based on asymmetric information, signalling mechanisms, or litigation risk cannot explain underpricing. In contrast to modern markets, the past market return had a negative influence on initial returns. Finally, we show that cash-flow relevant information contained in the corporate charter were readily factored in the first market price. Thus, the historical capital market differed from today's market, but seems to have been efficient.
Keywords: N23; N43; G18; 330; Initial public offerings; Financial history; Germany pre-1913; Underpricing; Wertpapieremission; Kapitalertrag; Börsenkurs; Effizienzmarktthese; Deutschland (bis 1945)